2019
DOI: 10.18632/oncotarget.27140
|View full text |Cite
|
Sign up to set email alerts
|

Excision repair cross-complementing group-1 (ERCC1) induction kinetics and polymorphism are markers of inferior outcome in patients with colorectal cancer treated with oxaliplatin

Abstract: BackgroundERCC1, a component of nucleotide excision repair pathway, is known to repair DNA breaks induced by platinum drugs. We sought to ascertain if ERCC1 expression dynamics and a single nucleotide polymorphism (SNP) rs11615 are biomarkers of sensitivity to oxaliplatin therapy in patients with colorectal cancer (CRC).MethodsWestern blot and qPCR for ERCC1 expression was performed from PBMCs isolated from patients receiving oxaliplatin-based therapy at specified timepoints. DNA was also isolated from 59 bior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 50 publications
0
12
1
Order By: Relevance
“…Several ERCC1 SNPs have been evaluated for their association with treatment outcome of oxaliplatin in CRC patients ( Supplementary Material—Table S1 ). The most commonly investigated nucleotide polymorphism is rs11615 ( Stoehlmacher et al., 2004 ; Ruzzo et al., 2007 ; Liang et al., 2008 ; Martinez-Balibrea et al., 2008 ; Pare et al., 2008 ; Chang et al., 2009 ; Chua et al., 2009 ; Chen et al., 2010 ; Liang et al., 2010 ; Huang et al., 2011 ; Lamas et al., 2011 ; Farina Sarasqueta et al., 2011 ; Li et al., 2012 ; Kumamoto et al., 2013 ; Nishina et al., 2013 ; van Huis-Tanja et al., 2014 ; Zaanan et al., 2014 ; Rao et al., 2019 ). A total of 10 studies showed a significant association between this polymorphism and treatment outcome ( Stoehlmacher et al., 2004 ; Ruzzo et al., 2007 ; Martinez-Balibrea et al., 2008 ; Pare et al., 2008 ; Chang et al., 2009 ; Chua et al., 2009 ; Chen et al., 2010 ; Huang et al., 2011 ; Li et al., 2012 ; Rao et al., 2019 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several ERCC1 SNPs have been evaluated for their association with treatment outcome of oxaliplatin in CRC patients ( Supplementary Material—Table S1 ). The most commonly investigated nucleotide polymorphism is rs11615 ( Stoehlmacher et al., 2004 ; Ruzzo et al., 2007 ; Liang et al., 2008 ; Martinez-Balibrea et al., 2008 ; Pare et al., 2008 ; Chang et al., 2009 ; Chua et al., 2009 ; Chen et al., 2010 ; Liang et al., 2010 ; Huang et al., 2011 ; Lamas et al., 2011 ; Farina Sarasqueta et al., 2011 ; Li et al., 2012 ; Kumamoto et al., 2013 ; Nishina et al., 2013 ; van Huis-Tanja et al., 2014 ; Zaanan et al., 2014 ; Rao et al., 2019 ). A total of 10 studies showed a significant association between this polymorphism and treatment outcome ( Stoehlmacher et al., 2004 ; Ruzzo et al., 2007 ; Martinez-Balibrea et al., 2008 ; Pare et al., 2008 ; Chang et al., 2009 ; Chua et al., 2009 ; Chen et al., 2010 ; Huang et al., 2011 ; Li et al., 2012 ; Rao et al., 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…The most commonly investigated nucleotide polymorphism is rs11615 ( Stoehlmacher et al., 2004 ; Ruzzo et al., 2007 ; Liang et al., 2008 ; Martinez-Balibrea et al., 2008 ; Pare et al., 2008 ; Chang et al., 2009 ; Chua et al., 2009 ; Chen et al., 2010 ; Liang et al., 2010 ; Huang et al., 2011 ; Lamas et al., 2011 ; Farina Sarasqueta et al., 2011 ; Li et al., 2012 ; Kumamoto et al., 2013 ; Nishina et al., 2013 ; van Huis-Tanja et al., 2014 ; Zaanan et al., 2014 ; Rao et al., 2019 ). A total of 10 studies showed a significant association between this polymorphism and treatment outcome ( Stoehlmacher et al., 2004 ; Ruzzo et al., 2007 ; Martinez-Balibrea et al., 2008 ; Pare et al., 2008 ; Chang et al., 2009 ; Chua et al., 2009 ; Chen et al., 2010 ; Huang et al., 2011 ; Li et al., 2012 ; Rao et al., 2019 ). Most studies, six out of 10, reported the mutant CC genotype to be the favorable genotype, with significantly better DFS, PFS, and OS ( Stoehlmacher et al., 2004 ; Chang et al., 2009 ; Chua et al., 2009 ; Chen et al., 2010 ; Huang et al., 2011 ; Li et al., 2012 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ERCC1 gene participates is the nucleotide excision pathway and is also connected with a gene specific repair which is realized by platinum containing anti-cancer drugs [27]. It has been found that high ERCC1 levels in patients with bladder cancer are associated with worse outcome [4,28].…”
Section: Excision Repair Cross Complementing Group 1 (Ercc1)mentioning
confidence: 99%
“…The excision repair cross-complement 1 (ERCC1) status appears to be a predictive and prognostic factor in this clinical setting. This nucleotide excision repair gene is involved in resistance to platinum compounds in different malignancies [103][104][105][106][107]. A study performed on 45 tissue samples from patients with recurrent or metastatic cervical cancer treated with CDDP + IFO with or without PTX, reported that high ERCC1 expression was an independent poor predictor of both PFS (HR = 2.473, 95% CI = 1.146-5.339) and OS (HR = 3.187, 95% CI = 1.346-7.546) [106].…”
Section: Combination Chemotherapymentioning
confidence: 99%